Vulnerable Groups at Lithuanian Labour Market - Moskvina, Julija; Okunevičiūtė Neverauskienė, Laima (Comparative Economic Research. Central and Eastern Europe, 2012)
Despite the economic growth and favourable situation in national labour market in 2004-2008 in Lithuania several groups of population still had restricted access to employment. The period of economic recession has revealed sore problems of vulnerable groups in the labor market. Based on statistical data and the research the dynamics of the situation of disabled, youth and older people situation in the labor market are examined in this article as well as the main obstacles to their participation. The increased number of the research aimed to analyse the situation of vulnerable groups in Lithuania and still persisting severe problems in national labour market stimulated to inventory recently cumulated knowledge about the groups that are at the high risk for unemployment. The research review covers studies conducted in the period between 2004 and 2010. It includes surveys carried out by competent researchers by the request of public authorities or other concerned authorities as well as doctoral dissertations. The groups of socially vulnerable people most often analysed in the labour market in Lithuania include the following: disabled, youth, and older people. The review showed that special research on labour market risk groups is the valuable search of information, whereas the shortage of statistical information has been noticed in the country. Further examination of the issues of the mechanisms to integrate and reintegrate the vulnerable groups into labour market is purposeful.